The Utility of Lymphatic Massage in Cosmetic Procedures - Troy Marxen; Orr Shauly; Pedram Goel; Tina Tsan; Rebecca Faria; Daniel J Gould (Aesthetic Surgery Journal Open Forum, 2023)
Abstract Lymphedema is a severe debilitating disease characterized by the accumulation of excessive protein-rich fluid in the interstitial space. Given the severe morbidity associated with this disease process, various surgical and nonsurgical treatment modalities have been developed to attempt to reduce the incidence and symptoms associated with lymphedema. Manual lymphatic drainage (MLD) is a component of complete decongestive therapy on-surgical treatment which has demonstrated benefit in reducing the development of lymphedema following surgery. Here we provide a review of literature on MLD and its potential mechanism of action. This paper aims to educate patients, physicians, and surgeons about MLD regarding its efficacy and utility in the treatment paradigm for lymphedema and to translate concepts from the treatment of lymphedema to cosmetic procedures. Level of Evidence: 5